Inhibition of angiogenesis and tumor growth by a novel 1, 4‐naphthoquinone derivative. Issue 3 (11th January 2019) - Murota, Hiroko; Shinya, Tomohiro; Nishiuchi, Arisa; Sakanaka, Mariko; Toda, Ken‐ichi; Ogata, Tokutaro; Hayama, Noboru; Kimachi, Tetsutaro; Takahashi, Satoru
Abstract: Hit, Lead & Candidate Discovery Antiangiogenesis therapy is a promising way for treatment of solid cancers, and many angiogenesis inhibitors that target vascular endothelial growth factor (VEGF) or its receptors have been developed. We explored novel antiangiogenic compounds other than anti‐VEGF drugs by screening our synthetic compound library and found that 6‐thiophen‐3‐yl‐2‐methoxy‐1, 4‐naphthoquinone (6‐TMNQ) had potential as a novel angiogenesis inhibitor. This paper describes the effects of 6‐TMNQ on angiogenesis and tumor growth in vitro and in vivo. 6‐TMNQ inhibited serum‐, VEGF‐, and basic fibroblast growth factor (bFGF)‐stimulated proliferation of endothelial cells in a concentration‐dependent manner, but had no effect on the proliferation of fibroblasts. VEGF‐induced activation of VEGF receptor‐2 in endothelial cells was not affected by the compound. 6‐TMNQ markedly abrogated both migration and tube formation of endothelial cells. Orally administered 6‐TMNQ inhibited angiogenesis in response to VEGF or bFGF in mice in a dose‐dependent manner. Furthermore, when tumor‐bearing mice were treated with 6‐TMNQ, increase in tumor size was significantly prevented due to inhibition of angiogenesis in the tumor tissues. These results demonstrate that 6‐TMNQ is an orally available compound that selectively inhibits endothelial cell proliferation and migration, and abrogates angiogenesis, resulting in the prevention of tumor growth. The mechanism of 6‐TMNQ action is different from that of conventional anti‐VEGF drugs.